CAC Model to Evaluate Teachers‟ Attitudes towards Technology Use in Their EFL Classrooms - Wahyuni, Sri (Language Circle: Journal of Language and Literature, 2018)
The rapid development of technology has altered so many aspects of people‘s private and social needs and activities including but not limited to communication, education, economy, commerce, and entertainment. In educational context, teachers and students‘ use of technology might be supported by several factors such as demand of academic and private use, increasing free internet access, as well as government and school policy on ICT-based instructions. In addition, use of technology among teachers is influenced by their attitudes. For years now, research focusing on teachers‘ attitudes towards technology use with Technology Acceptance Model (TAM) has been very much conducted to explore teachers‘ particular use of the digital devices and Web 2.0 technology. However, investigation of teachers‘ attitudes towards technology choices by using a Cognitive Affective Conative (CAC) Model by Schiffman & Kanuk (2004) in Jain (2014) is not yet very much done. Accordingly, the paper is an attempt to evaluate English teachers‘ attitudes towards technology use in their EFL classroom practices through CAC model of attitudes. Qualitative descriptive approach with a survey method was employed. The study involved English teachers of primary and secondary education in Central Java, Indonesia. The survey questionnaire was used to obtain the required research data. Finally, the pedagogical implication is presented.